Interfering With DNA Decondensation as a Strategy Against Mycobacteria - Scutigliani, Enzo M.; Scholl, Edwin R.; Grootemaat, Anita E.; Khanal, Sadhana; Kochan, Jakub A.; Krawczyk, Przemek M.; Reits, Eric A.; Garzan, Atefeh; Ngo, Huy X.; Green, Keith D.; Garneau-Tsodikova, Sylvie; Ruijter, Jan M.; et al. (Frontiers in Microbiology, 2018)
Tuberculosis is once again a major global threat, leading to more than 1 million deaths each year. Treatment options for tuberculosis patients are limited, expensive and characterized by severe side effects, especially in the case of multi-drug resistant forms. Uncovering novel vulnerabilities of the pathogen is crucial to generate new therapeutic strategies. Using high resolution microscopy techniques, we discovered one such vulnerability of Mycobacterium tuberculosis. We demonstrate that the DNA of M. tuberculosis can condense under stressful conditions such as starvation and antibiotic treatment. The DNA condensation is reversible and specific for viable bacteria. Based on these observations, we hypothesized that blocking the recovery from the condensed state could weaken the bacteria. We showed that after inducing DNA condensation, and subsequent blocking of acetylation of DNA binding proteins, the DNA localization in the bacteria is altered. Importantly under these conditions, Mycobacterium smegmatis did not replicate and its survival was significantly reduced. Our work demonstrates that agents that block recovery from the condensed state of the nucleoid can be exploited as antibiotic. The combination of fusidic acid and inhibition of acetylation of DNA binding proteins, via the Eis enzyme, potentiate the efficacy of fusidic acid by 10 and the Eis inhibitor to 1000 fold. Hence, we propose that successive treatment with antibiotics and drugs interfering with recovery from DNA-condensation constitutes a novel approach for treatment of tuberculosis and related bacterial infections.